Pengaruh Bauran Promosi terhadap Kesadaran Merek Pricebook - Faldhi Lazuardi; Satiri Satiri (Neolectura, 2022)
In business communication there are many strategies in promotion, one of which is the promotion mix. The purpose of this study was to determine the effect of the Promotion Mix on Brand Awareness on websites, social media, and Pricebook's YouTube channel. Pricebook is a startup company engaged in technology and information. Pricebook conveys information about product availability, online and offline stores, which are packaged in a unique and practical website. The method used is to conduct a survey that will be given to the object of website visitors as well as viewers and subscribers of Pricebook YouTube that will be studied. This research design aims to find the effect between two variables, namely Variable (X) is the Promotion Mix, while the variable (Y) is Brand Awareness. Respondents involved in this study were website visitors and Pricebook YouTube viewers/subscribers who had visited or watched Pricebook 3 times or more as many as 97 people. The sampling technique used non-probability sampling with the sampling technique method using purposive sampling. The results of this study indicate the Promotion Mix which consists of Advertising and Public Relations has a significant effect with 0.739 > 0.05, a strong correlation with a value of 0.686 and a positive effect of 47% on Brand Awareness which is supported by survey results and statistical calculations using SPSS software, in other words some of Pricebook's Brand Awareness is influenced by the Promotion Mix.